The N-terminal domain of Escherichia coli enzyme I of the phosphoenolpyruvate/glycose phosphotransferase system: molecular cloning and characterization. - Chauvin, F (1996)
The bacterial phosphoenolpyruvate/glycose phosphotransferase system (PTS) comprises a group of proteins that catalyze the transfer of the phosphoryl group from phosphoenolpyruvate (PEP) to sugars concomitant with their translocation. The first two steps of the phosphotransfer sequence are PEP <--> Enzyme I (EI) <--> HPr (the histidine-containing phosphocarrier protein). We have proposed that many functions of the PTS are regulated by EI, which undergoes a monomer/dimer transition. EI monomer (63.5 kDa) comprises two major domains: a flexible C-terminal domain (EI-C) and a protease-resistant, structurally stable N-terminal domain (EI-N) containing the active site His. Trypsin treatment of Salmonella typhimurium EI yielded EI-N, designated EI-N(t). Homogeneous recombinant Escherichia coli EI-N [i.e., EI-N(r)], has now been prepared in quantity, shows the expected thermodynamic unfolding properties and, similarly to EI-N(t), is phosphorylated by phospho-HPr, but not by PEP. In addition, binding of EI-N(r) to HPr was studied by isothermal titration calorimetry: K/a = 1.4 x 10(5) M(-1) and delta H = +8.8 kcal x mol(-1). Both values are comparable to those for HPr binding to intact EI. Fluorescence anisotropy [dansyl-EI-N(r)] and gel filtration of EI-N(r) show that it does not dimerize. These results emphasize the role of EI-C in dimerization and the regulation of intact EI.